Interview and workshop transcripts from harvesters in Fort Good Hope NWT about community hunts, barren-ground caribou hunts, and food-sharing practices, 2009-2010 - Cindy Dickson, Council Of Yukon First Nations; Roger McMillan, Department Of Resource Economics; Brenda Parlee, Department Of Resource Economics; Fort Good Hope Renewable Resources Council; Sahtu Renewable Resources Board (Canadian Cryospheric Information Network, 2016)
The data set consists of transcripts of interviews with hunters, and those involved in meat-sharing networks. Eight transcripts are included from community hunt participants; 5 transcripts are included from household hunters. A further 9 transcripts are included from those involved in sharing networks. One transcript is included from a hunt organizer. A public workshop transcript is also included that adds historical context to current hunting and sharing practices. : Purpose: Data was collected to understand community responses to the changing availability of barren-ground caribou, in terms of hunting and food-sharing. This involved looking at the history of community hunts, and comparing sharing networks between a community hunt and a series of household hunts. : Summary: Not Applicable